Comprehensive analytical profiling of soluble and bound phenolics of beans from selected underutilised legumes - Tan, Poh Hwa (2018)
Beans are seeds of leguminous plants and are rich in macronutrients and micronutrients such as polyphenols predominantly phenolic acids and flavonoids that may have health benefits arising from their antioxidant and other properties. Beans, especially from underutilised legumes, may play an important role in future world food supply. However, there has been limited investigation into the nutritional composition of underutilised beans compared with commercial beans such as soya bean. Therefore, this study aimed to improve the extraction, identification and quantification methodologies for characterizing soluble free, conjugated and insoluble bound phenolics from underutilised beans using high performance liquid chromatography (HPLC) and liquid chromatography – mass spectrophotometry (LC-MS).